Economic integration and redistributive taxation: a simple model with ambiguous results - Andreas Haufler; Alexander Klemm; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2006)
The rise in foreign direct investment and the increasing activity of multinational firms expose national corporate tax bases to cross-country profit shifting, but also lead to rising profitability of the corporate sector. We incorporate these two effects of economic integration into a simple political economy model where the median voter decides on a redistributive income tax rate. In this setting economic integration may raise or lower the equilibrium tax rate, depending on whether the higher excess burden of the tax or the larger redistributive gains from the perspective of the representative worker are the dominant effect. Our simple model holds several implications for future empirical work on the relationship between globalization and the effective rate of capital taxation.
Keywords: H20; F23; 330; Wirtschaftsintegration; Steuerpolitik; Einkommensumverteilung; Multinationales Unternehmen; Gewinnverlagerung; Theorie